Burnup performance of small-sized long-life CANDLE high temperature gas-cooled reactors with U–Th–Pa fuel. (May 2016) - Liem, Peng Hong; Tran, Hoai-Nam; Sekimoto, Hiroshi
Highlights: Burnup performance of small-sized long-life CANDLE HTGR with U–Th–Pa fuel was evaluated. Pa-231 partly serves as burnable poison at the beginning phase of CANDLE burning. Pa-231 plays the role of fertile nuclide at the later phase of CANDLE burning. U–Th–Pa fueled CANDLE HTGRs show better burnup performance (higher burnup and longer core life). U–Th–Pa fueled CANDLE HTGRs show lower axial power peaking. Abstract: The innovative CANDLE (C onstantA xial shape ofN eutron flux, nuclide densities and power shapeD uringL ife ofE nergy producing reactor) burnup strategy has been successfully applied to both fast and thermal reactors. In particular for thermal reactor applications, CANDLE block-type high temperature gas-cooled reactors (HTGRs) with either U–Pu or U–Th fuel cycle had been proposed and investigated for their simple and safe reactor operation, and the ease of designing a long life reactor. In this work, we investigated the use of Pa-231 mixed homogeneously in the (Th-232/U-233)O2 fuel kernel of the TRISO particles, that is the U–Th–Pa fuel, to obtain better CANDLE burnup performance. Some consideration on how to supply the required U-233 and Pa-231 was also thoroughly discussed. U–Th–Pa fuel decreases the required amount of natural Gd burnable poison in the fresh fuel for establishing a valid CANDLE HTGR design since Pa-231 has a large thermal absorption cross section. Besides the role as a burnable poison nuclide, Pa-231 also serves as a fertile nuclide during the CANDLE burning since Pa-231 is finally transmuted to a fissile U-233 nuclide. A promising analysis result shows that for U-233 and Pa-231 concentrations of 15 and 7.50 w/o, respectively, the discharged burnup can be increased from 138 (U-Th fuel) to 149 GWd/t. This extends the core life time about 16%, i.e. from 35 (U-Th fuel) to 41 years with CANDLE active core height of 800 cm and reactor thermal power of 30 MWth.